Transformational Leadership and School Management in Educational Institutions primary - Sardon Ari, Danitza Luisa (2017)
The research aimed to determine the relationship between the transformational leadership style used by the director and school management in primary educational institutions that apply the environmental approach at the city of Ilave, Puno in 2016.  The type of research was basic, with a non-experimental cross-sectional correlational design. It was considered a sample of 118 teachers who represented the total teachers population of the 04 primary educational institutions at the urban area of the city of Ilave. Data collection was carried out during the months of March and April. The results show a significant correlation between the dimensions of the type of transformational leadership and school management; thus the inspirational motivation had a value r = 0.492; the intellectual stimulation reached a value r = 0.72, the idealized influence a value r = 0.59; the individualized consideration had a value r = 0.62 and the performance of the director obtained a value r = 0.534. The research allows to conclude that there is a moderate positive correlation between the transformational leadership and the school management obtained in the statistical test, r = 0.681.